2014
DOI: 10.1038/npp.2014.170
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dopamine Transporter Functioning Induces High-Reward Risk-Preference Consistent with Bipolar Disorder

Abstract: Individuals with bipolar disorder (BD) exhibit deleterious decision making, negatively impacting their lives. Such aberrant decision making can be quantified using the Iowa Gambling Task (IGT), which requires choosing between advantageous and disadvantageous options based on different reward/punishment schedules. The mechanisms underlying this behavioral deficit are unknown, but may include the reduced dopamine transporter (DAT) functioning reported in BD patients. Using both human and mouse IGTs, we tested wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 61 publications
(92 reference statements)
17
83
0
Order By: Relevance
“…The similarity of task designs enables the assessment of mechanisms that might underlie abnormal decision-making in psychiatric patients. We have previously shown that patients with bipolar mania (BD) exhibit poor learning in the task compared with healthy subjects (HC; van Enkhuizen et al, 2014), consistent with other studies (C). Using these strategy assessment measures, it was clear that patients with BD preferred high reward sides after being given low rewards since they are less-likely to repeat preferences for low -but do so for high-rewards.…”
Section: Insights Into Abnormal Risky Decision-making In Humans From supporting
confidence: 70%
See 2 more Smart Citations
“…The similarity of task designs enables the assessment of mechanisms that might underlie abnormal decision-making in psychiatric patients. We have previously shown that patients with bipolar mania (BD) exhibit poor learning in the task compared with healthy subjects (HC; van Enkhuizen et al, 2014), consistent with other studies (C). Using these strategy assessment measures, it was clear that patients with BD preferred high reward sides after being given low rewards since they are less-likely to repeat preferences for low -but do so for high-rewards.…”
Section: Insights Into Abnormal Risky Decision-making In Humans From supporting
confidence: 70%
“…The IGT decks are stacked so that selecting from the high reward but higher punishment ("risky") sides result in overall loss over the 100 trials, whereas selecting from the low reward but lower punishment ("safe") sides result in overall gains. While performing the IGT, subjects tend to initially select the risky decks but rapidly (often by trial 20) switch to selecting from the safe decks, although there is a great deal of variability between subjects (Steingroever et al, 2013;van Enkhuizen et al, 2014). The IGT can be extremely useful when assessing the ability of subjects to withhold responding directed toward highly rewarding stimuli in order to obtain even greater gains in the future.…”
Section: Insights Into Abnormal Risky Decision-making In Humans From mentioning
confidence: 98%
See 1 more Smart Citation
“…Lower DAT functioning has been related to a hyperdopaminergic state and higher DAT to a lower dopaminergic activity (Laasonen-Balk et al, 1999;Van Enkhuizen et al, 2014). However, without optimal clearance due to lower DAT affinity or expression, DA release more readily diffuses into extrasynaptic space where it can also provide strong feedback inhibition and dampen DA turnover and thus the final outcome is likely dependent on modulatory variables such as D2S sensitivity (Dickinson et al, 1999;Jones et al, 1999).…”
Section: Da Reuptake and Recycling (Dopamine Transporter)mentioning
confidence: 98%
“…This task has since been adapted for use in both rats 68,69 and mice. 65 Unlike the probabilistic learning task however, the IGT utilizes more punishment and risk during task learning and so incorporates even more aspects of cognition that could confound behavioral results. Hence, making choices in this task based on feedback may provide a window into reward anticipation that links to motivation in patients with schizophrenia.…”
Section: Integrating Reward Feedback For Decision Makingmentioning
confidence: 99%